IMPLEMENTASI GOOGLE EARTH BERBASIS MODEL PJBL PADA PEMBELAJARAN GEOGRAFI DI SMAN 6 SOLOK SELATAN - Yuliani, Sri; Ahyuni (STKIP Subang, 2026)
Geographic Information Systems (GIS) are adequate for analyzing complex scientific and spatial phenomena in geography education. Google Earth is a geographic information tool for GIS-based learning in phase E with the topic of Remote Sensing Mapping and GIS Basics. This tool allows students to engage in simpler map creation. This study aims to determine the use of Google Earth media based on the Project Based Learning model on student learning outcomes at SMAN 6 Solok-Selatan. The research method used is quantitative with a quasi-experimental approach. Sampling was carried out using a purposive sampling technique. The sample used consisted of a control class and an experimental class with a total of 72 students. Data collection used pretest and posttest instruments in the form of essays. Data analysis used an independent sample t-test to determine the difference in pretest-posttest results between the two classes. The results showed a difference in learning outcomes of 87.75 for the experimental class, and 87.27 for the control class. This is proven by the value of the difference test results (t), from the calculation above obtained (2-tailed) of 0.000 smaller than 0.05, so it can be concluded that H₀ is rejected and Hₐ is accepted. The researcher's conclusion is that Google Earth media is more effective in improving student learning outcomes compared to conventional presentation media in Geography learning.